2014
DOI: 10.3390/molecules190710137
|View full text |Cite
|
Sign up to set email alerts
|

First Order Temperature Dependent Phase Transition in a Monoclinic Polymorph Crystal of 1,6-Hexanedioic Acid: An Interpretation Based on the Landau Theory Approach

Abstract: Abstract:Crystals of 1,6-hexanedioic acid (I) undergo a temperature-dependent reversible phase transition from monoclinic P2 1 /c at a temperature higher than the critical temperature (T c ) 130 K to another monoclinic P2 1 /c at temperature lower than T c . The phase transition is of first order, involving a discontinuity and a tripling of the b-axis at T c whereas the other unit cell parameters vary continuously. The transition is described by the phenomenological Landau theory. The crystal structure analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…We further grew single crystals and adopted x-ray crystallography to confirm that the solid precipitate is adipic acid (see fig. S2); our spectroscopic data are consistent with recently reported data (15). The isolated yield of solid adipic acid was ~53 (T 2) mol % at room temperature (an average of three runs, relative to the starting quantity of cyclohexane; the number in parentheses represents the stardard error).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…We further grew single crystals and adopted x-ray crystallography to confirm that the solid precipitate is adipic acid (see fig. S2); our spectroscopic data are consistent with recently reported data (15). The isolated yield of solid adipic acid was ~53 (T 2) mol % at room temperature (an average of three runs, relative to the starting quantity of cyclohexane; the number in parentheses represents the stardard error).…”
supporting
confidence: 90%
“…Thus, the approach of "cage encapsulation" of Au NPs in mesoporous supports is not advantageous for the stability of the active (atomically dispersed) Au sites. Other approaches-for example, AuCl 3 vapor produced by sublimation and introduced into various zeolites (14,15)-may be used to produce active Au(I)-Cl species for ambient-temperature NO reduction to N 2 O by CO. Mohamed and Ichikawa (16) have shown that the Au(I) species are the main active sites for the WGS reaction at temperatures as low as 50°C. Because these sites are not chloride-free (Au-Cl bonds exist) and have weak chemical binding to the zeolites, the Au(I) sites are easily reduced to inactive Au(0) and form Au NPs upon increasing the temperature to only 100°C (16).…”
Section: ) To Account For Formation Of Adipic Acid Via Selective C-h ...mentioning
confidence: 99%
“…A variety of catalysts like bimetallic catalysts, zeolitebased catalysts, supported catalysts, noble metal catalysts have been investigated by researchers for the conversion of biomass into adipic acid. Lin et al (2019) developed zirconia supported rhenium oxide catalyst and Pd/C catalyst for (Fun et al, 2014) conversion of D-glucaric acid-1,4-lactone to dibutylhexa-2,4dienedioate and 5 membered lactones that on hydrogenation gave dibutyl adipate. At 393 K and 24-hour reaction time, Dglucaric acid-1,4 -lactone that is a stable structure of glucaric acid was converted into dibutylhexa-2,4-dienedioate and 5 membered lactones.…”
Section: Chemocatalytic Conversion Of Biomass To Adipic Acidmentioning
confidence: 99%